2008
DOI: 10.1007/s00705-008-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

Two dicot-infecting mastreviruses (family Geminiviridae) occur in Pakistan

Abstract: Most mastreviruses (family Geminiviridae) infect monocotyledonous hosts and are transmitted by leafhopper vectors. Only two mastrevirus species, Tobacco yellow dwarf virus from Australia and Bean yellow dwarf virus (BeYDV) from South Africa, have been identified whose members infect dicotyledonous plants. We have identified two distinct mastreviruses in chickpea stunt disease (CSD)-affected chickpea originating from Pakistan. The first is an isolate of BeYDV, previously only known to occur in South Africa. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…Sequence analysis of the full-length amino acid sequence of the putative Rep of SsHADV-1 showed that it shares the highest sequence identity with the Reps of chickpea chlorotic dwarf virus (25), bean yellow dwarf virus (26), and tobacco yellow dwarf virus (27) (Table S2). These three viruses that infect dicotyledonous plants belong to the genus Mastrevirus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis of the full-length amino acid sequence of the putative Rep of SsHADV-1 showed that it shares the highest sequence identity with the Reps of chickpea chlorotic dwarf virus (25), bean yellow dwarf virus (26), and tobacco yellow dwarf virus (27) (Table S2). These three viruses that infect dicotyledonous plants belong to the genus Mastrevirus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of mastreviruses infect monocot plants and are transmitted by leafhoppers (33)(34)(35). The genome of mastreviruses comprises four open reading frames (ORFs).…”
mentioning
confidence: 99%
“…PCR products of~2.8 kb were cloned into the pTZ57R/ T vector (Fermentas). Subsequently, RCA using w29 DNA polymerase (Fermentas) was employed as described previously (Nahid et al, 2008). Concatameric RCA products were digested with restriction endonucleases to yield presumed monomeric virus (or virusassociated) components of either~2.8 or~1.4 kb.…”
Section: Methodsmentioning
confidence: 99%